Perfectionism, achievement goals and approaches to learning mathematics in higher education - Rovan, Daria (Array, 2007)
Drawing on 2 × 2 achievement goals framework (Elliot & McGregor, 2001), the aim of the present research was to examine relationship between perfectionism and achievement goals and to clarify the role of perfectionism and achievement goals in predicting students’ approaches to learning. Participants were 358 undergraduate students enrolled in an introductory-level mathematics course. Adaptive perfectionism was significantly related to mastery-approach, performance-approach goal, and mastery-avoidance goals, while maladaptive perfectionism was related to mastery-avoidance and performance avoidance goals. Adaptive perfectionism was significantly related to deep approach to studying and this relationship was partially mediated by mastery-approach goal and suppressed by performance-approach goal. Significant relation between adaptive perfectionism and strategic approach was partially mediated through mastery-approach goal. Adaptive perfectionism had significant negative effect on surface apathetic approach, which was completely mediated by mastery-approach goal and suppressed by mastery-avoidance goal. Maladaptive perfectionism was not related neither with deep or strategic approach, but it was positively related to surface approach. This relationship was only partially mediated by performance-avoidance goal. Results of our research support previous findings that mastery and approach orientation is consistently linked to positive outcomes. Adaptive perfectionism has proven to be more relevant in predicting achievement behavior, than maladaptive perfectionism. Adaptive perfectionism can lead to the pursuit of challenging goals and result in desirable outcomes, and maladaptive perfectionism can be to some extent debilitating as it can lead to adoption of less effective approach to learning.